Hubungan status gizi ibu hamil trimester III dengan kejadian BBLR - Sutrani Syarif; Elene Lahalima (THE JOURNAL OF Mother and Child Health Concerns, 2025)
Background: The occurrence of low-birth-weight babies can be caused by the nutritional status of the mother during pregnancy. There are several indicators that can be used to determine the nutritional status of pregnant women, including upper arm circumference (UAC), body mass index (BMI), and hemoglobin (Hb). Purpose: To determine the relationship between the nutritional status of pregnant women in the third trimester and low birth weight babies. Method: This study used a quantitative method with a cross-sectional approach. The sample consisted of 40 respondents using purposive sampling. The statistical test used was the chi-square test. Results: The study showed that the Chi-square Test yielded a p-value of 0.036 < 0.05, thus rejecting the null hypothesis (Ho). Conclusion: There is a relationship between the nutritional status of pregnant women in their third trimester and low birth weight.